1996
DOI: 10.1046/j.1365-2958.1996.d01-1719.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of Salmonella typhimurium invasion genes by a member of the phosphorylated response‐regulator superfamily

Abstract: The Salmonella typhimurium PhoP-repressed locus prgHIJK encodes components of a sec-independent type III secretion apparatus. This apparatus is composed of at least 17 proteins encoded on a 40 kb pathogenicity Island located at centisome 63 on the S. typhimurium chromosome. The secretion apparatus and some of its targets, SapB, SapC and SspD, are necessary for epithelial cell invasion. The transcription of many invasion genes, including prgHIJK, is coordinately activated by HilA, a transcription factor encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
207
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(216 citation statements)
references
References 53 publications
(94 reference statements)
7
207
1
1
Order By: Relevance
“…Tc, tetracycline resistant; Cm, chloramphenicol resistant. and P. viridiflava (Moolenaar et al, 1987;Rich et al, 1994;Liao et al, 1996;Johnston et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tc, tetracycline resistant; Cm, chloramphenicol resistant. and P. viridiflava (Moolenaar et al, 1987;Rich et al, 1994;Liao et al, 1996;Johnston et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Both the gacA and lemA genes are highly conserved in fluorescent pseudomonads (Liao et al, 1994;Corbell and Loper, 1995;Grewal et al, 1995). In Salmonella typhimurium, the gacA homologue sirA is essential for invasion and virulence (Johnston et al, 1996), and a gacA homologue is also known to be present in Escherichia coli (Moolenaar et al, 1987) and in Erwinia carotovora (Eriksson et al, 1996). In a human isolate of P. aeruginosa, a gacA mutation results in a significant reduction of pathogenicity in burnt mice as well as in infiltrated Arabidopsis plants (Rahme et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent search for ORFs homologous to ExpA and GacA identified a group of typical bacterial response regulator proteins with high homology (Fig. 2), including UvrY of E. coli (15), SirA of Salmonella typhimurium (21), and VarA of Vibrio cholerae (22) as well as highly homologous ORFs in the genomes of Klebsiella pneumoniae, Yersinia pestis, and Shewanella putrefaciens. The E. coli uvrY gene derives its name from a close linkage to the uvrC gene on a bicistronic transcript (14), a genomic organization shared by all of the above response regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most studies have been carried out using bacteria grown under so-called inducing conditions, namely high osmolarity and low oxygen conditions (LB containing 0.3 M NaCl without aeration). Studies of bacteria grown under these conditions have, to date, revealed that hilA expression is regulated by a complex array of regulatory systems including hilC/sirC/sprA (13)(14)(15), hilD (15), sirA/barA (16,17), fis (18,19), csrAB (16,20), envZ/ ompR (21), phoB (7), fadD (7), fliZ (7), hha (22), H-NS (19), and HU (19). Two of these genes, hilC and hilD, encode AraC-like transcriptional activators that activate hilA transcription by binding upstream of the hilA promoter DNA (15,23,24).…”
mentioning
confidence: 99%
“…Two of these genes, hilC and hilD, encode AraC-like transcriptional activators that activate hilA transcription by binding upstream of the hilA promoter DNA (15,23,24). Members of the phosphorylated response regulator superfamily involved in hilA expression include sirA/barA, envZ/ompR, phoR/ phoB, and phoP/phoQ (7,12,17,21). However, none of these regulatory systems has been shown to directly relay environmental signals to hilA expression.…”
mentioning
confidence: 99%